A clinical study on paediatric aero digestive foreign body in emergency department - D. K., Selvam; J., Nirmal Kumar; S., Anjan Kumar; P. S., Nagarajan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Foreign body ingestion and aspiration is a common clinical condition among the paediatric population. The management of the aero digestive foreign body requires clinical acumen, coupled with the radiological diagnosis and the necessary infrastructure for their management, it demands skill and expertise for removal of a foreign body. Methods: A retrospective study was carried in the department of Otorhinolaryngology, between December 2016- May 2017, at Institute of Child Health and Hospital for Children, Madras Medical College. 68 cases were analysis of the nature of the foreign body was done. All the patients reported to the emergency department and the ENT surgeon opinion sought with aim of maintaining airway. Clinical assessment, with history, radiographs were obtained to ascertain level and nature of the foreign body and prompt removal by oesophagoscopy/bronchoscopy/direct laryngoscopy under general anaesthesia. Results: The study of 68 children who reported with history /suspicion of foreign body ingestion/aspiration. There were 32 boys and 36 females, 37 cases of foreign body ingestion and 31 cases of foreign body aspiration. The most common foreign body in digestive tract was coin in 26 cases and peanut in the airway. Conclusions: Foreign bodies in aero digestive tract in paediatric age group, is a common problem encountered by the otorhinolaryngologist. Careful assessment, clinical evaluation, radiological investigations with effective management in emergency department prompt removal of the foreign body in the aero digestive tract will lead to reduced mortality and morbidity.